Analyzing the Pump Diesel and Gasoline Prices on Inflation in Pakistan: A New Evidence from Non-Linear ARDL (Journal of Social Sciences Review, 2023)
Maintaining inflation is one of the prime goals of the macroeconomic policy executed through the country's central bank. The persistence of inflation is considered a serious problem in developing countries because it erodes the standard of living of the majority of people. Nowadays, researchers are showing interest in energy price shocks as one of the drivers of inflation. So, the present study examines the role of pump diesel and pump gasoline prices on inflation controlling real exchange deprecation and urbanization using NARDL from 1990 to 2020. The result shows that the pump domestic diesel prices and pump domestic gasoline prices have a positively asymmetric impact on inflation in Pakistan. In contrast, real exchange deprecation and urbanization positively affect inflation. This study recommended that the government decrease the dependence on imported energy and focus on cheaper and domestic energy resources to fulfil the growing energy demand.
Keywords: Inflation; Pump Diesel Price; Pump Gasoline Prices; Real Exchange Rate; NARDL